Pulmonary Mycobacterium abscessus complex in children with cystic fibrosis: A practical management guideline. (18th March 2019) - Andrew, Eden C; Connell, Tom; Robinson, Phil; Curtis, Nigel; Massie, John; Robertson, Colin; Harrison, Joanne; Shanthikumar, Shivanthan; Bryant, Penelope A; Starr, Mike; Steer, Andrew; Ranganathan, Sarath; et al.
Abstract: The treatment of Mycobacterium abscessus complex (MABSC) pulmonary infections is an emerging challenge in patients with cystic fibrosis (CF). Multidrug therapy for prolonged durations is required and carries the significant burden of drug‐related toxicity, cost and selective pressure for multiresistant bacteria. International guidelines acknowledge that clinical and in vitro data to support treatment regimens are limited, particularly in children. As part of a collaboration between the infectious diseases and respiratory units at our institution, we have developed a modified treatment guideline that aims to balance the aims of MABSC eradication and slowing disease progression with minimising drug toxicity and resistance. The outcomes of this treatment approach will be monitored and reported. In this manuscript, we discuss the available evidence for treatment choices and present our treatment guideline for paediatric patients with CF and MABSC infection.